Pediatric Collections : Vaping: Effects and Solutions - (AAP), American Academy of Pediatrics (Pediatric collections., 2020)
Electronic cigarettes are the tobacco products most commonly used by youths in the United States. The use of e-cigarettes, also known as vaping or JUULing, is a public health epidemic. This collection offers reviews and research to assist pediatric health care providers in identifying and treating adolescent use and exposure to e-cigarettes.